Assessment And Financial Analysis For Citrus (Citrus Sinensis) Improvement Program In Jambi - Izhar, Lutfi; Hernita, Desi; Salwati, Salwati; Suharyon, Suharyon (Journal of Tropical Horticulture, 2020)
The agricultural problems currently cover-up with limited land, water, infrastructure, production facilities and infrastructure, access to finance and institutions. These problems cause the quantity and quality of agricultural products to be stumpy. One effort that can eliminate these problems is through the assessment of a comprehensive, integrated agricultural development program. Â The objectives of this study was: (1) to determine the amount of citrus farming income, and (2) to analyze the economic and institutional feasibility of citrus farming in Bunga Tanjung Village, Betara District, west Tanjung Jabung region. This study was conducted in Bunga Tanjung Village, Betara District, West Tanjung Jabung, Jambi, from 2017-2019. Approach to the activities through coordination and program integration from the Regional Government. Efforts to increase the production of citrus plants are currently experiencing challenges due to doubtful economic viability. Data collected in this study includes primary data in the form of information from farmers and secondary data such as a profile of study area, demographics, social and economic potential data. Primary data was collected by interviewed farmers using a questionnaire. The sample was randomly determined citrus farmer population with 40 respondents. Data analysis techniques include tabulation analysis used to recognize the farmer's economic conditions and feasibility. The results of this study indicated that citrus productivity had increased continuously by applying environmentally friendly cultivation technology i.g. Fertilizing, controlling pests and diseases, removing water shoots, pruning shapes, and pruning unproductive branches. Citrus production of non-demonstration plots was 3.145 kg, and demonstration was 4.960 kg, there was an increase of 1.815 kg or 36.59% with an average of R/C ratio for demonstration plots was 2.51 while non-demonstration citrus of 2.20. This means that the cultivation of the citrus plant is feasible to continue.